2017
DOI: 10.1080/10826084.2017.1322406
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of Advantages and Disadvantages of Drinking Among Individuals With the Lived Experience of Homelessness and Alcohol Use Disorders

Abstract: Background: AUDs are more prevalent among people who are homeless than in the general population. Thus, homeless individuals experience disproportionately high levels of alcohol-related problems and associated publicly funded criminal justice and health-care system utilization. Available treatment services, however, are not effective at engaging and treating this population. To better tailor treatment services to their needs, it is imperative we understand this population’s perceptions of their alcohol use. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Among emergency department patients, those who were homeless reported greater levels of unhealthy alcohol use in the past year (44%); both current homelessness and experiences of homelessness within the past 12 months were significant predictors of unhealthy alcohol use [29]. The probable reasons for alcohol use problems among individuals experiencing homelessness include alcohol acting as a perceived agent for coping with psychological distress and/or physical pain, and the social advantage of having a sense of "community" around street culture and drinking [30]. Alcohol use problems and the myriad comorbidities that accompany them are strong contributors to the initiation and maintenance of homelessness, and have been associated with numerous adverse individual and societal consequences and high rates of morbidity and mortality among both domiciled and homeless adults [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Among emergency department patients, those who were homeless reported greater levels of unhealthy alcohol use in the past year (44%); both current homelessness and experiences of homelessness within the past 12 months were significant predictors of unhealthy alcohol use [29]. The probable reasons for alcohol use problems among individuals experiencing homelessness include alcohol acting as a perceived agent for coping with psychological distress and/or physical pain, and the social advantage of having a sense of "community" around street culture and drinking [30]. Alcohol use problems and the myriad comorbidities that accompany them are strong contributors to the initiation and maintenance of homelessness, and have been associated with numerous adverse individual and societal consequences and high rates of morbidity and mortality among both domiciled and homeless adults [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…This study applies Qualitative -Content Analysis (CA) method. CA is a qualitative research method used to interpret the content of text data through a systematic classification process involving coding and identifying themes (Collins et al, 2018). This method is a widely used qualitative research technique (Hsieh & Shannon, 2005;Igwe, Lock & Rugara, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Nóżka et al (2013) indicated that these additional problems are: housing, personal difficulties (diseases, inability to cope with relationships, aggression, lack of goals in life), social (family problems, rejection), economic (lack of work, debts), and institutional (dependence on social welfare, difficulty in accessing help). Moreover, Leickly et al (2017), Collins et al (2018), andDoran et al (2018) wrote that addiction to alcohol or other substances is a significant problem for people experiencing homelessness. Additionally, Collins et al (2018) indicated that there is a lack of research on the perception of alcohol by the homeless, emphasising that there are also no studies concerning the negative effects of alcohol consumption by the homeless.…”
Section: Homelessnessmentioning
confidence: 99%
“…Homelessness and alcohol addiction have combined, for decades, the interests of various scientific fields, disciplines and their sub-disciplines, such as education, social work and disability studies. In social sciences, the world-wide quantitative, psychological and clinically-orientated research gives a rich insight into the context of homelessness and addiction to alcohol (Leickly et al, 2017;Collins et al, 2018;Doran et al, 2018). However, the constructivist and interpretivist approaches, as well as secondary qualitative data analysis of homeless masculinity and addictions to alcohol are still underrepresented in Poland.…”
Section: Introductionmentioning
confidence: 99%